TRANSFORMING SOCIAL WORK: CONTEXTUALISED SOCIAL WORK EDUCATION IN SOUTH AFRICA - Turton, Yasmin; Schmid, Jeanette (Social Work/Maatskaplike Werk, 2020)
Despite significant transformation efforts in South African social welfare, social work education still inducts students into prevailing paradigms. Critics suggest that dominant social work is ineffective in that it is culturally inappropriate, marginalises other knowledges, overlooks structural issues, is expensive and is mismatched to local needs. The term “contextualised social work education” as used in this article incorporates the local focus on decolonisation/decoloniality and indigenisation. This article highlights the work of 12 South African educators in offering contextualised social work education. In exemplifying their decolonising work, the imperatives, challenges, supports and future pathways/options identified by participants are discussed.